2022
DOI: 10.1002/ueg2.12276
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic enzyme treatment in chronic pancreatitis: Quality of management and adherence to guidelines–A cross‐sectional observational study

Abstract: Objectives Pancreatic exocrine insufficiency (PEI) is a common complication in patients with chronic pancreatitis (CP), leading to increased morbidity and mortality if not treated adequately. Pancreatic enzyme replacement therapy|pancreas enzyme replacement therapy (PERT) is the cornerstone in treatment of patients with PEI. In the present study, we use data from the Scandinavian Baltic Pancreatic Club database to examine adherence of PERT according to United European Gastroenterology evidence‐based guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In addition to PERT improving digestion and absorption in patients with EPI, studies have shown improvements in weight trends, quality of life, and even mortality in patients with chronic pancreatitis taking PERT. 45,[54][55][56] Several studies also found prolonged survival in patients with pancreatic cancer. [57][58][59] Giordano et al conducted a retrospective observational trial and demonstrated PERT and dietary interventions had a direct and significant impact on overall survival.…”
Section: Pertmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to PERT improving digestion and absorption in patients with EPI, studies have shown improvements in weight trends, quality of life, and even mortality in patients with chronic pancreatitis taking PERT. 45,[54][55][56] Several studies also found prolonged survival in patients with pancreatic cancer. [57][58][59] Giordano et al conducted a retrospective observational trial and demonstrated PERT and dietary interventions had a direct and significant impact on overall survival.…”
Section: Pertmentioning
confidence: 99%
“…72 Studies have demonstrated a wide range of dosing practices and often found PERT was underutilized and inadequately dosed. 39,45,54,73 The American College of Gastroenterology recommends a starting dose of at least 40,000-50,000 USP units of lipase per meal. 60 Randomized controlled trials have found enzyme doses of 72,000-75,000 USP units of lipase with meals and 36,000-50,000 USP units of lipase with snacks to be effective for adequate fat absorption (see Table 4).…”
Section: Pert Dosingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite known benefits, infrequent prescription and underuse of PERT are common [6]. Existing studies also show that adherence to evidence-based guidelines in the medical management of EPI remains suboptimal [7][8][9]. Therefore, we sought to analyze various factors associated with the use of PERT in patients with EPI.…”
Section: Underutilization Of Pancreatic Enzyme Replacement Therapy In...mentioning
confidence: 99%
“…Patients with PEI can present with non-specific gastrointestinal (GI) symptoms suggesting maldigestion, including steatorrhea, weight loss, abdominal pain, and bloating ( 2 ). Due to the character of the symptoms, as well as to the potential diversity of the underlying disease, PEI is underdiagnosed, instauration of treatment may be delayed, and overall management not optimal ( 3 , 4 ). Furthermore, PEI can have a negative impact of outcome ( 5 ) and pancreatic enzyme replacement therapy (PERT) can improve both survival and quality of life (QoL) ( 6 , 7 ).…”
mentioning
confidence: 99%